A Proposal to Strengthen the Values of Solidarity and Empathy of 4-5-year old Children Attending a Private Institution, in the Province of Heredia (Costa Rica), Through Playful-creative Workshops - Vargas Mora, Mónika (2013)
The main purpose of this project was to analyze how solidarity and empathy may be strengthened in 4-5-year old children through playful-creative workshops. The project was conducted in a private institution, in the province of Heredia, Costa Rica. This qualitative research was composed of three stages. First, a diagnostic stage helped us to identify the background of participants in relation to the values being studied; it included interviews and observation of participants. In the second stage, playful-creative workshops were put into practice to strength the values. The last stage was a comparative analysis of the information collected before and after carrying out the activities; it helped us to see if the children’s experience in relation to the values of empathy and solidarity was influenced by the workshops. One of the main conclusions is that by sharing and working with students through this methodology, children became more aware of the feelings of other people, and it improved their relations with other children.